Income Inequality in Thailand: A Relative Poverty Approach - Meemon1, Natthani (Animo Repository, 2022)
This study explored income inequality in Thailand using the OECD’s relative poverty indicator. Based on 2013 and 2017 data from Thailand and the OECD, we compared trends in poverty between countries. Then, by selecting the working-age population in Thailand, we examined several socioeconomic determinants of poverty. The results indicate that the relative poverty rate in Thailand was relatively high compared to the OECD countries and was considerably higher for children and older adults. Among the working-age population, unemployed individuals and informal-sector employees had a persistently higher risk of relative poverty. These results imply that income inequality in Thailand depends largely on the country’s employment situation. People who are not employed or engaged in any economic activity have a high chance of being impoverished, which can increase income inequality. From another viewpoint, the situation could indicate that the current welfare and social protection systems for people not directly related to employment in Thailand are inadequate compared to the systems in OECD countries. Based on the results, we recommend that the government should strengthen current welfare policies for these people. The child allowance for low-income workers and the employment benefit for retirement or termination, which are limited to formal-sector employees and their families, should be extended to workers in the informal employment sector. For older adults, the Old-Age Allowance should raise the currently inadequate pension amount to a realistic level that reflects the cost of living. In the long term, these fragmented policies should be integrated into a national pension policy that considers the country’s economic situation and social consensus.